Evaluation of the TREX1 gene in a large multi-ancestral lupus cohort (2011)
Systemic lupus erythematosus (SLE) is a prototypic autoimmune disorder with a complex pathogenesis in which genetic, hormonal and environmental factors have a role. Rare mutations in the TREX1 gene, the major mammalian 3?-5? exonuclease, have been reported in sporadic SLE cases. Some of these mutations have also been identified in a rare pediatric neurological condition featuring an inflammatory encephalopathy known as Aicardi- Goutières syndrome (AGS). We sought to investigate the frequency of these mutations in a large multi-ancestral cohort of SLE cases and controls. A total of 40 single-nucleotide polymorphisms (SNPs), including both common and rare variants, across the TREX1 gene, were evaluated in 8370 patients with SLE and 7490 control subjects. Stringent quality control procedures were applied, and principal components and admixture proportions were calculated to identify outliers for removal from analysis. Population-based case-control association analyses were performed. P-values, false-discovery rate q values, and odds ratios (OR) with 95% confidence intervals (CI) were calculated. The estimated frequency of TREX1 mutations in our lupus cohort was 0.5%. Five heterozygous mutations were detected at the Y305C polymorphism in European lupus cases but none were observed in European controls. Five African cases incurred heterozygous mutations at the E266G polymorphism and, again, none were observed in the African controls. A rare homozygous R114H mutation was identified in one Asian SLE patient, whereas all genotypes at this mutation in previous reports for SLE were heterozygous. Analysis of common TREX1 SNPs (minor allele frequency (MAF)10%) revealed a relatively common risk haplotype in European SLE patients with neurological manifestations, especially seizures, with a frequency of 58% in lupus cases compared with 45% in normal controls (P0.0008, OR1.73, 95% CI1.25-2.39). Finally, the presence or absence of specific autoantibodies in certain populations produced significant genetic associations. For example, a strong association with anti-nRNP was observed in the European cohort at a coding synonymous variant rs56203834 (P2.99E13, OR5.2, 95% CI3.18-8.56). Our data confirm and expand previous reports and provide additional support for the involvement of TREX1 in lupus pathogenesis. © 2011 Macmillan Publishers Limited All rights reserved.